Healing Environment sebagai Upaya Penyembuhan Psikologis melalui Desain Rumah Sakit - Siti Bidaria Paputungan; Oktaviana Bilqiis Otoluwa; Bayu Kurnia Sandy Malahika; Amelia Ahmad (Jurnal Psikologi, 2025)
The design of hospitals plays a vital role in supporting patient recovery, both physically and psychologically. However, many hospitals in Indonesia, particularly in Gorontalo, have yet to apply design principles aligned with the Healing Environment concept. This study aims to analyze the design issues of hospitals in Gorontalo and provide recommendations based on environmental psychology theories. The research method used is a descriptive qualitative case study. The results show that poor lighting, inadequate ventilation, spatial configurations that hinder social interaction, and lack of green space are the main barriers to creating a healing environment. Recommendations include the addition of natural elements, calming color schemes, and space designs that encourage social interaction. The Healing Environment concept has proven to be relevant in enhancing comfort, reducing stress, and accelerating patient recovery.